(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: The objective of this scientific work was focused on formulation, optimization and evaluation of loteprednol-loaded spanlastic nanocarriers for effective treatment of ocular inflammation with enhanced transcorneal drug permeation, prolonged corneal residence time, and sustained drug release profile. Materials and Methods: The spanlastic nanocarriers of loteprednol was prepared by ethanol injection method using Span 60 and Tween 80 as vesicular components. A 23 factorial design was employed in the optimization studies selecting independent variables such as Span 60, Tween 80, and drug content, whereas, the response variables such as particle size, polydispersity index, zeta potential, entrapment efficiency, and cumulative % drug release. The optimized formulation was evaluated for various in vitro and ex vivo parameters. Results and Discussion: The optimized formulation of spanlastic nanocarriers of loteprednol was found to have 207.4 nm particle size, 0.41 polydispersity index, −0.62 mV zeta potential, and 58.23% entrapment efficiency. The cumulative % drug release was 98.45% during 8-h period exhibiting sustained release and Korsmeyer-Peppas model release kinetics. The ex vivo drug permeation study across goat eye cornea exhibited apparent permeability (Papp) of 11.95 cm/min-1 and steady-state flux (Jss)of 19.45 mg/cm2 min-1which was >5 times higher than marketed product. The developed formulation maintained its physical characteristics and possessed all desired product quality attributes in the ideal range. Conclusion: The developed loteprednol loaded spanlastic nanocarriers demonstrated all the quality parameters very close to the software predicted values and also exhibited enhanced transcorneal drug permeation which would lead to higher ocular drug bioavailability and need of less frequent drug administration in effective management of ocular inflammation.